2005
DOI: 10.1007/s11177-005-0053-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual and population variation in cercariae of bird schistosomes of the Trichobilharzia ocellata species group as revealed with the polymerase chain reaction

Abstract: The polymerase chain reaction with arbitrary (RAPD-PCR) or specific primers was used to study the population variation and to identify the species in cercariae of schistosomes of the Trichobilharzia ocellata species group (Trematoda, Schistosomatidae). In total, 28 cercariae were obtained from two spontaneously invaded mollusks Lymnaea stagnalis (LS) and L. ovata (LO), which were collected in different ponds of Moscow. RAPD-PCR was carried out with two arbitrary primers, OPA9 and OPB11, which each detected dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…They did not provide any further data or analysis. Semyenova et al (2005) found some evidence for generation of heterogeneity in another schistosome genus, Trichobilharzia. We know of no other explicit reports of somatic mutation in trematodes.…”
Section: Discussionmentioning
confidence: 96%
“…They did not provide any further data or analysis. Semyenova et al (2005) found some evidence for generation of heterogeneity in another schistosome genus, Trichobilharzia. We know of no other explicit reports of somatic mutation in trematodes.…”
Section: Discussionmentioning
confidence: 96%
“…Previously, using two random primers, we observed cercariae RAPD variability between two Trichobilharzia species-T. szidati and T. franki (Semenova et al 2005). In addition, we demonstrated the utility of RAPD to study population genetic structure of Bucephalus polymorphus (Trematoda: Bucephalidae) using cercariae from daughter sporocysts (Korsunenko et al 2009).…”
Section: Introductionmentioning
confidence: 84%
“…Most of the effort has been conducted using three gene regions. To date, the nuclear ribosomal DNA D1-D2 regions of 28S, the internal transcribed spacer (ITS) region, and the mitochondrial cox1 gene have been tested as molecular markers for systematics (40,63,67,69,70,105,123,248,249,251), epidemiology (252), and diagnostics (121,253). Sequencing of gene regions such as the nuclear ITS region and the mitochondrial cox1 gene not only has linked life cycle stages but also has suggested that our recognition of the diversity of avian schistosomes continues to grow (10, 12, 40, 65-67, 69, 70, 105, 129, 133, 135).…”
Section: Detection and Identification Of Avian Schistosomesmentioning
confidence: 99%